Pembentukan Karakter Lulusan Melalui Pembelajaran Bahasa Arab di Pondok Modern Gontor Ponorogo dan Pondok Pesantren Lirboyo Kediri - Bakar, M. Yunus Abu (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
Learning Arabic in Indonesia has been starting from the entry of Islam into the country. Learning starts from Arabic as the language of worship, where Muslims worship with readings in Arabic, the Arabic language learning begins with learning to read the Qur'an. From then thrive on learning Arabic to understand religious texts and then the language as a medium of communication that are taught at various educational institutions from the classic to the modern. Two boarding schools, namely: Pondok Modern Darussalam Gontor and Pondok Pesantren Lirboyo, is an example of the boarding school in different models of Arabic learning, in terms of learning materials, methods and learning strategies which would also affect the formation of the character of graduates that is constructed by each boarding schools, and different in the level of use of the Arabic language in the context of life. In general, learning Arabic Pondok Modern Gontor located on the cluster model of integrative and shape that are learning Arabic as a whole, and spawned four language skills (competencies), namely: Al-Qira 'ah, As-Sima'ah, Al-Muhadathah and Al-Kitabah. While learning Arabic in Pondok Pesantren Lirboyo located on the cluster model of instrumental and shape are learning a language for understanding the content of the books turath, and creates two skills, namely: Al-Qira'ah, and As-Sima'ah.